LTBP4 deficiency induces MRC1 + /CD44 + macrophages to drive cancer progression in preclinical colorectal cancer models - Songtao Ji; Shuya Du; Ge Miao; Xiaohua Yang; Haojia Wang; Xuemei Li; Wanqi Ma; Dan Wei; Tianyu Cao; Mingzhen Zhou; Jianing Yu; Xiangshu Cheng; et al. (Science Translational Medicine, 2026)
The tumor microenvironment is crucial for cancer progression, but the mechanisms underlying the tumor-immune cell interactions in it remain poorly understood. Here, we identified latent transforming growth factor–β (TGFβ) binding protein 4 (LTBP4) deficiency in colorectal cancer (CRC) as a critical driver that reprogrammed tumor-associated macrophages (TAMs) and induced a distinct subset, which promoted tumor progression by coordinating immune evasion and extracellular matrix (ECM) remodeling. Clinically, LTBP4 deficiency correlated with CRC progression and poor patient survival. Ltbp4 knockout markedly promoted tumor growth and metastasis in immunocompetent mice, an effect attenuated in immunodeficient hosts, establishing the essential role of host immunity in mediating the effects of LTBP4 deficiency. Single-cell RNA sequencing revealed that LTBP4 deficiency induced a mannose receptor C-type 1–positive (MRC1 + )/CD44 + TAM subset and correlated with reduced CD8 + T cell infiltration. Mechanistically, LTBP4 deficiency increased active TGFβ1 levels, which acted in a paracrine manner to up-regulate MRC1 in TAMs, whereas autocrine signaling induced HAS2 (hyaluronan synthase 2) expression and hyaluronan production to increase CD44. CD44 signaling in TAMs up-regulated matrix metalloproteinases for collagen degradation, whereas MRC1 mediated collagen internalization, cooperatively remodeling the ECM to facilitate tumor invasion. The TGFβ1-driven MRC1 + /CD44 + TAMs further suppressed CD8 + T cell function by diminishing the C-X-C motif chemokine ligand 16-C-X-C motif chemokine receptor 6 (CXCL16-CXCR6) axis. Therapeutically, targeted depleting MRC1 + /CD44 + TAMs enhanced the efficacy of PD-1 (programmed cell death–1) blockade in LTBP4-deficient tumors. Our study positions LTBP4 as a key modulator of tumor progression and reveals a therapeutic strategy for LTBP4-deficient CRC.